Tren Layanan Referensi Virtual Studi Kualitatif Pada 12 Website Perpustakaan di Pulau Jawa - Katrin Setio Devi; Indira Irawati (Institut Agama Islam Negeri (IAIN) Curup, 2020)
The virtual reference service (VRS) has been implemented by some libraries in Indonesia. This study aims to identify trends in VRS in some libraries in the Java Island. This research is a qualitative study using descriptive analysis presented as a percentage, then elaborated again with narration or description associated with the field and theory. Using purposive sampling technique, selected 12 libraries to be analyzed on the website. The sample consists of public libraries and special libraries. The results form 12 library samples found to bring trends in the form of presenting referral services if sorted from the most used by the library are email (91%), web forms (75%), chat references (67%), and SMS (8%). Both email and web form used for VSR is using the library's public email. Chat references available on the web library use the Tawk Live Chat App, add on Dalet Galaxy, Whatsapp and Line. VRS in SMS form is only used by the National Library. Email is the most common format used as a communication tool in VRS followed by web forms, chat references and SMS. The results of this study can be used as material for consideration to develop format of VRS in Indonesian libraries